Vpliv razvoja kartografskih tehnik na podobe zemljevidov slovenskega ozemlja od 16. do 19. stoletja - Fridl, Jerneja (Knjižnica, 2011)
Purpose: the paper presents the most important maps of the present-day Slovenian territory from 16th to 19th century contributed by many foreign and local authors. Due to technological, social, political, economic, cultural, and ideological conditions their image was constantly changing. Some of them are highlighting the key turning points in a centuries-long cartographic development. Methodology/approach: the survey is based on the analysis of primary sources held in the Map Collection of the National and University Library as well as in Geographical museum of Scientific Research Centre of the Slovenian Academy of Sciences and Arts. The existing secondary sources, particularly the literature and the results of selected projects, are also critically evaluated. From the scientific point of view the paper is interdisciplinary although its content mostly affects the scope of cartography. Results: the inductive method offers conclusions on the role of maps as a medium for transferring different information. Maps are presented either in the light of their communicative value or in the light of using modern cartographic principles. Maps as graphic images captured on paper demonstrate technological development of selected historical periods and characteristics of different countries, their people, and especially the emergence of individual countries and national border changes. Research limitation: due to limitations in the length of the study text we focus only on the selected items of the cartographic collection and their authors. As usually, we were unable to avoid important cartographers, such as Valvasor, Florjančič and Kozler. The major national cartographic materials held by a two institutions, the National and University Library and GIAM ZRC SAZU Geographical Museum are exposed. Originality/practical implications: the originality of this paper lies mainly in the fact that we deal with maps and their authors together with the impact of technological development on the image of the maps. We also expose their informative value as they reflect not only the cartographer's views about the world, but also the current values of the society.
Keywords: cartography; Florjančič, Ivan Dizma, 1691-ok.1757; historical presentations; kartografija; maps; Slovenia; Slovenija; Valvasor, Janez Vajkard, 1641-1693; zemljevidi; zgodovinski pregledi